The numerical CFD investigation of hub losses of pushing air propellers with tandem joined blades of small sized unmanned aerial vehicles - Kulyk, Mykola; Kirchu, Fedir; Hussein, Hanesh (Technology audit and production reserves, 2019)
The object of study is a pushing tandem propeller with joined blades. When analyzing the characteristics of pushing propellers, it was found that one of the problem areas is a decrease in their effectiveness due to a decrease in axial thrust, which occurs due to the formation of a zone of reduced pressure (vacuum) in the area of the hub and the propeller spinner. For pushing propellers of the classic design, the reduction in efficiency reaches a level of 1–2 %. For tandem propellers, such information is not available due to the fact that such structures are practically not used on aircraft. However, in recent years, potential opportunities and advantages over classical propellers have increased the interest of researchers in the issues of their use in aircraft. It is noted that the tandem propeller should have greater hub losses compared to the classic propeller, since the diffuser of the interscapular channel is greater. To assess the value and establish the factors influencing the formation of hub losses of tandem propellers, studies were carried out using numerical gas dynamics methods. During the study, to simulate the operation of the tandem propeller, we used the ANSYS CFX software package, which implements an algorithm for solving unsteady Reynolds averaged Navier-Stokes equations closed by the SST Menter turbulence model. As a result of modeling, it was found that the level of secondary losses in the hub part of a tandem propeller is significantly affected by the mutual arrangement of the profiles of the first and second blades. When the angle of profiles installation of the second blades row increases, the vacuum in the hub part and in the spinner zone increases, which leads to the appearance of reverse thrust and reduces the thrust of the propeller by an average of 3–4 %. The obtained results confirmed the assumption that the hub losses of the tandem propellers directly depend on the diffusivity of the interscapular canal in the blades root part. Consideration of research results in the design of tandem propellers will reduce hub losses and increase the efficiency of the propellers.